A facile strategy for the growth of high-quality tungsten disulfide crystals mediated by oxygen-deficient oxide precursors. Issue 26 (24th June 2022) - Miakota, Denys I.; Unocic, Raymond R.; Bertoldo, Fabian; Ghimire, Ganesh; Engberg, Sara; Geohegan, David; Thygesen, Kristian S.; Canulescu, Stela
Abstract : Chemical vapor deposition (CVD) has been established as a versatile route for the large-scale synthesis of transition metal dichalcogenides, such as tungsten disulfide (WS2 ). Abstract : Chemical vapor deposition (CVD) has been established as a versatile route for the large-scale synthesis of transition metal dichalcogenides, such as tungsten disulfide (WS2 ). Yet, the precursor composition's role on the CVD process remains largely unknown and remains to be explored. Here, we employ Pulsed Laser Deposition (PLD) in a two-stage approach to tune the oxygen content in the tungsten oxide (WO3− x ) precursors and demonstrate the presence of oxygen vacancies in the oxide films leads to a more facile conversion from WO3− x to WS2 . Using a joint study based on ab initio density functional theory (DFT) calculations and experimental observations, we unravel that the oxygen vacancies in WO3− x can serve as niches through which sulfur atoms enter the lattice and facilitate an efficient conversion into WS2 crystals. By solely modulating the precursor stoichiometry, the photoluminescence emission of WS2 crystals can be significantly enhanced. Atomic resolution scanning transmission electron microscopy imaging (STEM) reveals that tungsten vacancies are the dominant intrinsic defects in mono- and bilayers WS2 . Moreover, bi- and multilayer WS2 crystals derived from oxides with a high V 0 content exhibit dominant AA′/AB or AA(A…) stacking orientations. The atomic resolution images reveal local strain buildup in bilayer WS2 due to competing effects of complex grain boundaries. Our study provides means to tune the precursor composition to control the lateral growth of TMDs while revealing insights into the different pathways for forming grain boundaries in bilayer WS2 .